Life cycle and epizootiology of Amblyospora ferocis (Microspora: Amblyosporidae) in the mosquito Psorophora ferox (Diptera: Culicidae) - Micieli, María Victoria (2003)
A natural population of Psorophora ferox (Humbold, 1820) infected with the microsporidium Amblyospora ferocis García et Becnel, 1994 was sampled weekly during a seven-month survey in Punta Lara, Buenos Aires Province, Argentina. The sequence of development of A. ferocis in larvae of P. ferox leading to the formation of meiospores followed the developmental pathway previously reported for various species of Amblyospora. The natural prevalence of A. ferocis in the larval population of P. ferox ranged from 0.4% to 13.8%. Spores were detected in the ovaries of field-collected females of P. ferox and were shown to be responsible for transovarial transmission of A. ferocis to the next generation of mosquito larvae in laboratory tests. These spores were binucleate and slightly pyriform in shape. The prevalence of A. ferocis in the adult population ranged from 2.7% to 13.9%. Data on effects of the infection on female fecundity showed that infected field-collected adults of P. ferox laid an average of 47.6 ± 6.5 eggs of which 35.8% ± 4.1% hatched. Uninfected field-collected adults of P. ferox laid 82.8 ± 6.8 eggs of which 64.1% ± 5.5% hatched. Six species of copepods living together with P. ferox were fed meiospores from field-infected larvae but none became infected. Horizontal transmission of A. ferocis to P. ferox larvae remains unknown.